Comparison of the Microsatellite Distribution Patterns in the Genomes of Euarchontoglires at the Taxonomic Level - Song, Xuhao; Yang, Tingbang; Zhang, Xinyi; Yuan, Ying; Yan, Xianghui; Wei, Yi; Zhang, Jun; Zhou, Caiquan (Frontiers in Genetics, 2021)
Microsatellite or simple sequence repeat (SSR) instability within genes can induce genetic variation. The SSR signatures remain largely unknown in different clades within Euarchontoglires, one of the most successful mammalian radiations. Here, we conducted a genome-wide characterization of microsatellite distribution patterns at different taxonomic levels in 153 Euarchontoglires genomes. Our results showed that the abundance and density of the SSRs were significantly positively correlated with primate genome size, but no significant relationship with the genome size of rodents was found. Furthermore, a higher level of complexity for perfect SSR (P-SSR) attributes was observed in rodents than in primates. The most frequent type of P-SSR was the mononucleotide P-SSR in the genomes of primates, tree shrews, and colugos, while mononucleotide or dinucleotide motif types were dominant in the genomes of rodents and lagomorphs. Furthermore, (A)n was the most abundant motif in primate genomes, but (A)n, (AC)n, or (AG)n was the most abundant motif in rodent genomes which even varied within the same genus. The GC content and the repeat copy numbers of P-SSRs varied in different species when compared at different taxonomic levels, reflecting underlying differences in SSR mutation processes. Notably, the CDSs containing P-SSRs were categorized by functions and pathways using Gene Ontology and Kyoto Encyclopedia of Genes and Genomes annotations, highlighting their roles in transcription regulation. Generally, this work will aid future studies of the functional roles of the taxonomic features of microsatellites during the evolution of mammals in Euarchontoglires.